Design of Hand Task Assist Device for Perceptual Disabilities - S. Hariedha, M. Jagannath, V.E. Jayanthi, G. Sudhanthira,P. Sutha,S. Usha (International Journal of Advanced Science and Technology, 2020)
In general the hand gestures are used in the system of recognition. Sign Language Converter (SLC) is designed to solve the language barrier between the users and rest of the world. The proposed work presents a prototype system for recognizing the hand gesture to normal people in order to communicate more effectively with perceptually disabled people. In foresaid research work, digital image processing is used to reduce the problems in gesture recognition. American Sign Language (ASL) alphabets are used to recognize the gestures for this system development. Template matching techniques is introduced for recognizing the sign language and its output is represented in the form of voice. Arduino UNO board is used to convert text into gesture and voice.